Gender inequality in multidimensional welfare deprivation in West Africa : the case of Burkina Faso and Togo - Agbodji, A; Batana, Y; Ouedraogo, D (Oxford Poverty & Human Development Initiative (OPHI), 2013)
The importance of gender equality is reflected not only in the Millennium Development Goals (MDGs) but also in the World Bank’s Gender Action Plan launched in 2007, as well as in other treaties and actions undertaken at regional and international levels. Unlike other gender poverty studies, which are mostly based on monetary measurement, the present study employs a counting approach to examine gender issues in Burkina Faso and Togo using household surveys, EICVM (2009/2010) and CWIQ (2011), respectively. Focusing on six dimensions (housing, basic utilities, assets, education, employment and access to credit) largely recognized as MDG targets, the main findings of the study indicate that, overall, individuals are most deprived in education in Burkina Faso, while the reverse situation is true in Togo. Gender inequality is observed in all. The situation is also marked by regional disparities. Moreover, the assessment of dimensional contributions shows different patterns for each country. While employment proves to be the main contributor to gender inequality in Burkina Faso, three dimensions (assets, access to credit and employment) account together for most of the total contribution to gender inequality in Togo. There is also a positive correlation between multidimensional deprivation and women’s ages in Burkina Faso, whereas by contrast both measures seem to be uncorrelated in Togo.